Optimisation of zinc oxide surge arrester design using gravitational search algorithm and imperialist competitive algorithm - Syahirah Abd Halim; Azah Mohamed; Nor Azwan Mohamed Kamari; Afida Ayob; Ab Halim Abu Bakar; Hazlee Azil Illias (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Reducing electric field stress near the energised end of surge arresters is very important because it may increase the lifetime of the highly stressed ZnO column in vicinity of the high voltage electrode. Most of previous works were based on manufacturers’ procedures and trial and error method to improve the surge arrester designs. In this work, optimisation of ZnO surge arrester design models using Gravitational Search Algorithm (GSA) and Imperialist Competitive Algorithm (ICA) is proposed. The surge arrester models were developed using finite element analysis (FEA) and used to determine the electric field distribution. The optimisation methods were used to determine the arrester design parameters which yield the minimum electric field stress surrounding the energized end of the surge arresters. GSA is less complex since it requires only two parameters to be adjusted i.e. mass and velocity while ICA demonstrates faster convergence and better achievement of global optimum. The performance of the proposed methods was then compared with the manufacturer’s test data and previously developed methods.